THERMAL AND GASDYNAMIC MODEL OF CRUSTAL EARTHQUAKES - Ponomarev A.S. (My University, 1989)
A thermal and gasdynamic (TGD) model of earthquakes is described. The model is based on Sadovskiy's idea that the energy of earthquakes is linearly related to the focal volume and the definition of a new role of supercritical mantle fluid, as an energy carrier that seals the porous rock around the periphery of a flow. We find that natural porosity ε = 0.01 to 0.001 of rock filled with a supercritical fluid is completely sufficient to produce foci of energy and volume consistent with the estimate obtained in field geophysical studies. The supercritical fluid emanating from the mantle behaves as a strong rock solvent in the lower thermobaric horizons of the crust, but as it rises into zones with lower pressure and temperature, it becomes demineralized in the pores by depositing 'plugs' of salts and minerals, forming foci whose external sealed surfaces coincide with the periphery of the fluid flow, while the volumetric energy density in the focus depends on the fluid pressure.